(untitled) (CIPEEX, 2022)
ABSTRACT: LEISURE IS A FUNDAMENTAL RIGHT, PROVIDED FOR IN ARTICLE 6 OF THE FEDERAL CONSTITUTION,WHICH "TRANSLATES INTO A PRIVILEGED DIMENSION OF HUMAN EXPRESSION WITHIN A CONQUERED TIMEMATERIALIZED THROUGH A CREATIVE PERSONAL EXPERIENCE, OF PLEASURE THAT IS NOT REPEATED IN SPACETIME WHOSE MAIN AXIS IS PLAYFULNESS" (BRUMANTE, 1998). THE FEDERAL CONSTITUTIONESTABLISHES AN ORDER FOR THE STATE TO ENFORCE THE RIGHT TO LEISURE FOR ALL CITIZENS IN THE NATIONAL,STATE, AND MUNICIPAL SPHERES (BRASIL, 1998). HOWEVER, THIS RIGHT OFTEN PRIORITIZES THE NOBLEAREAS OF THIS MUNICIPALITY AND EXCLUDES THE VULNERABLE AREAS OF THE CITY. IN THIS SENSE, THEPRESENT WORK AIMS AT EVALUATING AND ANALYZING WHETHER THIS RIGHT HAS BEEN EQUALLY PROVIDED TO THE POPULATION BY THE PUBLIC POWER OF SENADOR CANEDO. TO REACH THE DESIRED RESULTS IT WASESTABLISHED THE FOLLOWING SPECIFIC OBJECTIVES: A) DISCUSS THE CONSTITUTIONAL PROVISION ABOUT THERIGHT TO LEISURE; B) DISPOSE ABOUT AND CONCEPTUALIZE LEGALLY AND DOCTRINALLY LEISURE; C) ANALYZEWHETHER THE MUNICIPAL GOVERNMENT OF SENADOR CANEDO, GO, PROVIDES EQUAL ACCESS TO LEISURETO ALL AREAS OF THE CITY. TO THIS END, THE FOLLOWING QUESTION WAS ESTABLISHED AS THE CENTRALPROBLEM: DO ALL AREAS OF THE CITY OF SENADOR CANEDO PROVIDE EQUAL ACCESS TO LEISURE? THEMETHODOLOGICAL CONSTRUCT USED TO OBTAIN DATA FOR THIS RESEARCH CONSISTED OF FIELD, EXPLORATORYAND EXPLANATORY RESEARCH, BESIDES BIBLIOGRAPHICAL RESEARCH. THE PRESENT STUDY FINDS A HIGHDEGREE OF IMPORTANCE IN THE LEGAL, SCIENTIFIC AND SOCIAL FIELDS, AS IT AIMS AT APPROACHING THERIGHT OF ACCESSIBILITY TO LEISURE IN AREAS OF SOCIAL VULNERABILITY IN THE CITY OF SENADOR CANEDO, ASUBJECT THAT HAS NEVER BEEN EXPLORED, BRINGING SCIENTIFIC AND INFORMATIVE CONTRIBUTIONS TO THEPOPULATION, AND MAY EVEN BE THE OBJECT OF A LEGISLATIVE PROPOSAL. THUS, IT IS IMPORTANT TODISCUSS THE PROPOSED THEME, SINCE THE RESULTS OBTAINED POINT TO A CLEAR DISCREPANCY BETWEENTHE PUBLIC LEISURE OFFERED IN MORE FAVORED AREAS AND THE OUTSKIRTS, WHICH HARMS NOT ONLY THECONSTITUTIONAL RIGHT TO LEISURE, BUT ALSO THE CONSTITUTIONAL RIGHT TO EQUALITY "EVERYONE IS EQUALBEFORE THE LAW, WITHOUT DISTINCTION" (BRASIL 1988). THUS, THE RESULTS OBTAINED WERE: A) IN THENEIGHBORHOODS STUDIED (BURITI, PARASO 1 AND 2) THERE IS A TOTAL LACK OF PUBLIC POLICIES RELATED TO LEISURE; B) IN NOBLE AREAS OF THE CITY THERE ARE PUBLIC POLICIES RELATED TO LEISURE, WHICH SHOWS A VIOLATION OF THE CONSTITUTIONAL RIGHT TO EQUALITY AND LEISURE; C) THUS, IT IS NECESSARY AN ACTIVEPOSTURE OF THE MUNICIPAL GOVERNMENT TO SOLVE THIS PROBLEM. IT IS UNDERSTOOD THAT, FROM THE DATA THAT WILL BE REVEALED THROUGH THIS STUDY, IT IS UP TO THE GOVERNMENT AND THE COMMUNITY TO RETHINK THE APPLICABILITY OF THE MUNICIPAL BUDGET, CONSIDERING THAT THE PROMOTION OF LEISURE CONTRIBUTES SIGNIFICANTLY TO THE REDUCTION OF VIOLENCE